Salivary Gland Dysfunction and Dysphagia in Post-Chemoradiotherapy Head and Neck Malignancy Patients - Susyana Tamin; Marlinda Adham; Elvie Z. Rachmawati; Sabda Ardiantara; Eka D. Safitri (Faculty of Medicine Universitas Indonesia, 2021)
Radiotherapy can potentially cause damage to the salivary gland, muscles, and nerve that is important to oropharyngeal swallow, leading to xerostomia and dysphagia. Reporting a case of radiotheraphy-induced xerostomia and dysphagia in HNC patients. A 34 years old man with NPC stage IV B (T4N3M0) came with difficulty swallowing, dryness in the throat and mouth, coughing while eating and drinking, choking, hoarseness, and pain when swallowing. The patient had done 14 times of radiation administration with a total dose of 60 Gy with conformal 3D radiation technique. The amount of saliva measured 0.02 ml/minute. A standing secretion was found in the vallecula, right and left piriformis and postkrioid sinuses in preswallowing assessment. The presence of penetration or aspiration of secretions into the airway were detected. The patient was diagnosed with neurogenic dysphagia and advised to use NGT for diet and consult medical rehabilitation. Literature searching was conducted on March 31, 2021 in the 3 journal database, including PubMed, Cochrane, and EBSCOhost, using particular keywords based on PICO. The inclusion criteria were full text article, observational studies, case-control, cohort, randomized controlled trial, systematic review, written in English, and studies investigating the correlation between HNC patient with radiotherapy and dysphagia or xerostomia. There were 3 systematic reviews, 1 cohort, and 2 cross-sectional studies investigating the correlation between chemoradiotherapy in head and neck cancer and xerostomia/dysphagia. Chemoradiotherapy correlated with dysphagia and xerostomia in head and neck cancer. Xerostomia and disfagia were prevalent in HNC patients after radiotherapy. Besides, there was association between the dose of radiotherapy and incidence or severity of xerostomia and dysphagia.